1998
DOI: 10.1001/archsurg.133.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hypoadrenalism During Surgical Critical Illness

Abstract: Objective: To report the cortisol levels in 6 patients during and after severe inflammation. Design: Patients with severe inflammatory disease had basal and stimulated (cosyntropin) serum cortisol levels determined at the time of severe and less severe inflammation. Setting: Intensive care unit and wards of a tertiary care center. Patients: Six patients with continued evidence of severe inflammation, despite aggressive management of the underlying inflammatory disease. Interventions: Five of 6 patients receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
7
1
Order By: Relevance
“…36 Unlike our patients, however, humans with transient postsurgical hypoadrenalism had severe inflammation and sepsis, and their baseline cortisol concentrations increased as inflammation decreased. 36 Because cortisol concentrations in dogs are much lower than in humans, applying criteria of inadequate adrenal function from the human literature is inappropriate. We therefore evaluated adrenal function based on previously published criteria ( 30 ng/mL increase over baseline) for septic dogs 10 and by using a relatively conservative estimate of 50% increase in post-ACTH cortisol over baseline.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…36 Unlike our patients, however, humans with transient postsurgical hypoadrenalism had severe inflammation and sepsis, and their baseline cortisol concentrations increased as inflammation decreased. 36 Because cortisol concentrations in dogs are much lower than in humans, applying criteria of inadequate adrenal function from the human literature is inappropriate. We therefore evaluated adrenal function based on previously published criteria ( 30 ng/mL increase over baseline) for septic dogs 10 and by using a relatively conservative estimate of 50% increase in post-ACTH cortisol over baseline.…”
Section: Discussioncontrasting
confidence: 62%
“…The most common objective criterion for diagnosis of RAI in humans is post‐ACTH cortisol concentration <180 ng/mL or change in cortisol concentration <90 ng/mL 11 . Treatment with hydrocortisone has also been recommended for humans with transient postsurgical hypoadrenalism when post‐ACTH concentrations did not double 36 . Unlike our patients, however, humans with transient postsurgical hypoadrenalism had severe inflammation and sepsis, and their baseline cortisol concentrations increased as inflammation decreased 36 .…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Serum cortisols and their response to ACTH are sometimes attenuated in severe inflammatory conditions or septic shock. 12,21 For those patients who survive their critical illness, adrenal function usually normalizes. In some studies supplemental glucocorticoids are supplied, and in others they are not.…”
Section: Discussionmentioning
confidence: 99%
“…But it was found that in most cases of adrenal infiltration with malignant cells still residual adrenal tissue is capable of maintaining needs even with stress [21,24]; chronic infections such as Fungal infection e.g. histoplasmosis and paracoccidiomycosis in endemic areas [25]. And others such as syphilis and African trypanosomiasis.…”
Section: Non Immune Causes Of Primary Adrenal Insufficiencymentioning
confidence: 99%